Prevention: the science and art of promoting healthy child and adolescent development - Borkowski, John G. (Brookes, 2006)
The art and science of prevention research : principles of effective programs / John G. Borkowski, Carol E. Akai, and Leann A. Smith -- Promoting infant growth and development / Lane E. Volpe and Willow A. Wetherall -- Preventing early developmental delay / Leann A. Smith, Jody S. Nicholson, and Julie N. Schatz -- Preventing child maltreatment / Julie N. Schatz -- Preventing youth violence / Shannon S. Carothers and Chelsea M. Weaver -- Preventing adolescent substance abuse / Amber M. Grundy and Stacey B. Scott -- Preventing risky sexual behavior / Chelsea M. Weaver, Elizabeth H. Blodgett, and Shannon S. Carothers -- Preventing dating violence / Kimberly S. Howard -- Marital conflict and the aftermath of divorce : prevention programs for families / Patricia M. Mitchell, W. Brad Faircloth, and Peggy S. Keller -- Where do we go from here? : a synthesis of science and art / John G. Borkowski and Chelsea M. Weaver